PENGARUH MODEL DISCOVERY LEARNING TERHADAP PERKEMBANGAN KOGNITIF SISWA KELAS IV SEKOLAH DASAR - Diyatmika, Utama; Suarni, Ni Ketut; Margunayasa, I Gede (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of the research is to determine the effect of using the discovery learning model of the students’ cognitive development on science subjects at grade IV in elementary schools. The research applied a quantitative approach with an experimental design. The research involved fourth grade students at SD Negeri 06 Karangasem. This research involved two classes, namely the experimental class and the control class. Tests is used as instruments in this research, namely pretest and posttest. Where the pretest is used on students before being given treatment to the two classes. While the posttest is used after the treatment is carried out. Preparation of tests based on criteria C1-C6. The research samples were classes IVA and IVB. The t test calculations obtained tcount= 6.515 and ttable= 2.000 and this means tcount>ttable. There is a significant influence on the use of the discovery learning model on the class IV students’ cognitive development on science subjects with material force on objects in SD Negeri 06 Karangasem.